I have worked the problem, but I keep getting the wrong answer. I've also looked at some other similar questions from here, but I still don't understand what I'm doing incorrectly.


First, the derivations I got:

$y=C_1 x^{2}+C_2 x^{3}$



$\Longrightarrow C_2=\dfrac{y''-2C_1}{6x}$

Then, I started substituting:

$y'=2C_1 x+3\left(\dfrac{y''-2C_1}{6x}\right) x^2=2C_1 x+\left(\dfrac{1}{2}\right) xy''-C_1 x$

$y'=C_1x+\left(\dfrac{1}{2}\right) xy''$

$\Longrightarrow C_1=\dfrac{y'}{x}-\dfrac{y''}{2}$

When I plugged $C_1$ and $C_2$ back into $y=C_1 x^{2}+C_2 x^{3}$:

$y=\left(\dfrac{y'}{x}-\dfrac{y''}{2}\right) x^2+\left(\dfrac{y''-2\left(\dfrac{y'}{x}-\dfrac{y''}{2}\right)}{6x}\right) x^3$

And when I simplify, I end up with:

$y=\dfrac{2xy'}{3}-\dfrac{x^2 y''}{2}$

But I'm being told this is incorrect. Is there a different approach to this problem and/or have I made a mistake somewhere?

Thanks in advance!

  • 1
    $\begingroup$ Your simplification at the end is incorrect. You missed $\frac{1}{3}x^2y''$, hence it should be $\displaystyle y=\frac{2xy'}{3}-\frac{x^2y''}{6}$. Rather than that your solution is perfect. $\endgroup$ – Galc127 Aug 31 '16 at 4:20
  • $\begingroup$ Thank you! I saw where I made a mistake. $\endgroup$ – nexicon Aug 31 '16 at 4:46

You want to perform differentiations that remove the constants directly. So I would probably start with dividing everything by $x^2$ and differentiating the result, like thus:

$\begin{eqnarray}y & = & C_1 x^2 + C_2 x^3 \\ \frac{y}{x^2} & = & C_1 + C_2 x \\ \frac{d}{dx}\left(yx^{-2}\right) & = & \frac{d}{dx}\left(C_1 + C_2 x\right) \\ y'x^{-2} - 2yx^{-3} & = & C_2 \\ \frac{d}{dx}\left(y'x^{-2} - 2yx^{-3}\right) & = & \frac{d}{dx} C_2 \\ y''x^{-2} - 4y'x^{-3} + 6yx^{-4} & = & 0 \\ y'' - 4y'x^{-1} + 6yx^{-2} & = & 0\\ y'' & = & \frac{4y'}{x} - \frac{6y}{x^2} \end{eqnarray}$

Which is, I believe, equivalent to the corrected answer @Galc127 has suggested, but where I've focused on the highest order derivative of $y$.

  • $\begingroup$ Thanks, I never thought about doing it that way! $\endgroup$ – nexicon Aug 31 '16 at 4:47

It is true that $y=C_1x^2+C_2x^3\Rightarrow y=\frac{2xy'}{3}-\frac{x^2y''}{2}$. But conversely, it doesn't hold. Maybe because of this reason, your answer is not incorrect. The correct answer should be such that $y=C_1x^2+C_2x^3\Leftrightarrow$correct answer

  • $\begingroup$ No, it does not hold. If $y=C_1x^2+C_2x^3$, then $y'=2C_1x+3C_2x^2,y''=2C_1+6C_2x$ and then $$\frac{2xy'}{3}-\frac{x^2y''}{2}=\frac{2x(2C_1x+3C_2x^2)}{3}-\frac{x^2(2C_1+6C_2x)}{2}=\frac{1}{3}C_1x^2-C_2x^3\neq y$$ $\endgroup$ – Galc127 Aug 31 '16 at 4:24

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.